2015
DOI: 10.1161/hypertensionaha.115.05435
|View full text |Cite
|
Sign up to set email alerts
|

Greater Sensitivity of Blood Pressure Than Renal Toxicity to Tyrosine Kinase Receptor Inhibition With Sunitinib

Abstract: Abstract-Hypertension and renal injury are off-target effects of sunitinib, a tyrosine kinase receptor inhibitor used for the treatment of various tumor types. Importantly, these untoward effects are accompanied by activation of the endothelin system. Here, we set up a study to explore the dose dependency of these side effects. Normotensive Wistar Kyoto rats were exposed to 3 different doses of sunitinib or vehicle. After 8 days, rats were euthanized. Telemetrically measured blood pressure rose dose dependentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 34 publications
(58 reference statements)
7
39
0
Order By: Relevance
“…B: CD31 immunostainings of cross sections of the renal outer medulla at P12. Representative pictured are shown at a magnification of ϫ10/ϫ40; scale bars ϭ 200/100 m. ficient VEGFR2 inhibition is likely since growth attenuation and proteinuria was observed as previously described (18,29,33). Whole body growth was impaired stronger than renal growth as judged from the increased kidney/body weight ratio and the lower protein/dsDNA ratio in kidney tissue.…”
supporting
confidence: 56%
“…B: CD31 immunostainings of cross sections of the renal outer medulla at P12. Representative pictured are shown at a magnification of ϫ10/ϫ40; scale bars ϭ 200/100 m. ficient VEGFR2 inhibition is likely since growth attenuation and proteinuria was observed as previously described (18,29,33). Whole body growth was impaired stronger than renal growth as judged from the increased kidney/body weight ratio and the lower protein/dsDNA ratio in kidney tissue.…”
supporting
confidence: 56%
“…It has recently been shown that renal cGMP excretion is reduced in rats with sunitinib‐induced hypertension,25, 26 which may be a consequence of low renal NO bioavailability 11, 16, 24. In keeping with this finding, the phosphodiesterase inhibitor sildenafil failed to attenuate the arterial pressure rise in sunitinib‐treated rats 26.…”
Section: Introductionmentioning
confidence: 75%
“…We focus on the early phase of developing sunitinib‐induced hypertension to investigate mechanisms that lead to the arterial pressure rise with minimum interference by factors that may be secondary to vascular and renal damage 11, 25. A recent study in patients with renal cell carcinoma34 showed that the sunitinib‐induced arterial pressure rise is not preceded by reduced acetylcholine or sodium nitroprusside–induced forearm vasodilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group also observed a decrease in urinary excretion of NO metabolites or its effector molecule cGMP in rats exposed to sunitinib. 35,36 In contrast, using the Langendorff-isolated heart model, the vasodilator response to bradykinin and sodium nitroprusside were both diminished as was the vasoconstrictor response to angiotensin II. 37 These findings suggest a general BRAF indicates proto-oncogene; cFms, colony forming factor; c-KIT, receptor tyrosine kinase protein; c-MET, hepatocyte growth factor receptor; CSF1, colony stimulating factor; EGFR, epithelial growth factor receptor; FDA, Food and Drug Administration; FGF, fibroblast growth factor; Flt3, FMS-like tyrosine kinase 3; LEK, proto-oncogene; MAPK, mitogen-activated protein kinase; PDGFR, platelet-derived growth factor receptor; RET, proto-oncogene; RAF, protooncogene; VEGF, vascular endothelial growth factor; and VEGFR, VEGF receptor.…”
Section: Mechanism Of Hypertension Decrease In No Bioavailabilitymentioning
confidence: 98%